Carbohydrate-Based Vaccines Methods and Protocols - Lepenies, Bernd; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume summarizes current cutting-edge methods related to carbohydrate-based vaccines, from the identification of a suitable carbohydrate antigen via the preparation of glycoconjugate vaccines to the characterization of vaccine candidates for their use in pre-clinical and clinical studies. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Carbohydrate-Based Vaccines: Methods and Protocols aims to be a valuable manual that will facilitate research in the field of carbohydrate-based vaccines.
Carbohydrate-based Vaccines: An Overview -- Glycans as Vaccine Antigens and Adjuvants: Immunological Considerations -- The Glycan Array Platform as a Tool to Identify Carbohydrate Antigens -- Antibody-carbohydrate Recognition from Docked Ensembles using the AutoMap Procedure -- Generation of Monoclonal Antibodies against Defined Oligosaccharide Antigens -- Murine Whole-Blood Opsonophagocytosis Assay to Evaluate Protection by Antibodies Raised Against Encapsulated Extracellular Bacteria -- Determination of N-linked Glycosylation in Viral Glycoproteins by Negative Ion Mass Spectrometry and Ion Mobility -- N-Glycosylation Fingerprinting of Viral Glycoproteins by xCGE-LIF -- Temporary Conversion of Protein Amino Groups To Azides: A Synthetic Strategy For Glycoconjugate Vaccines -- Gold Nanoparticles as Carriers For Synthetic Glycoconjugate Vaccines -- Identification and Characterization of Carbohydrate-Based Adjuvants -- Characterization of Carbohydrate Vaccines by NMR Spectroscopy Francesco Berti and Neil Ravenscroft -- Characterisation of Capsular Polysaccharides and Their Glycoconjugates by Hydrodynamic Methods -- Glycoconjugate Vaccines: The Regulatory Framework.
Keywords: Immunology; Immunology